Impacts of increased temperatures on floral rewards and pollinator interactions: a meta-analysis - Alquichire-Rojas, Shirley; Escobedo, Víctor M.; González-Teuber, Marcia (Frontiers in Plant Science, 2024)
Flowering plants produce pollinator rewards such as nectar and pollen, whose quantity and quality usually depend on the whole-plant state under specific environmental conditions. Increasing aridity and temperature linked to climate change may force plants to allocate fewer resources to these traits, potentially disrupting plant-pollinator interactions. In this study, for the first time, both quantitative review (vote-counting procedure) and meta-analytic approach were used to assess the implications of increased temperatures linked to global warming on floral rewards, including nectar (sugar concentration, content, and volume) and pollen (germination and viability), as well as on pollinator visits. Furthermore, we explored whether observed effects of warming are related either to temperature range, plant type (wild vs crop), or study approach (greenhouse vs field experiments). We also assessed the correlations between elevated temperatures and the characteristics that were affected by the temperature range. The results of the vote-counting technique showed that higher temperatures led to a decrease in floral rewards but did not affect the number of pollinator visits. Concurrently, metaanalysis detected adverse effects of warming on pollen germination and viability.Warming effects depended on the plant type for pollen germination and viability, on study approach for nectar sugar concentration and pollen germination, and on temperature range for pollen germination and pollinator visits. Additionally, we found that pollen germination and pollinator visits significantly decreased as temperature range increased.Our results showed that global warming affects floral rewards in both wild and crop plants, providing insights into the effects of changing climatic conditions on plant-pollinator interactions and pollination services.